Global climate change, diet, and the complex relationship between human host and microbiome: Towards an integrated picture. (8th April 2021) - Catania, Francesco; Baedke, Jan; Fábregas‐Tejeda, Alejandro; Nieves Delgado, Abigail; Vitali, Valerio; Long, Le Anh Nguyen
Abstract: Dietary changes can alter the human microbiome with potential detrimental consequences for health. Given that environment, health, and evolution are interconnected, we ask: Could diet‐driven microbiome perturbations have consequences that extend beyond their immediate impact on human health? We address this question in the context of the urgent health challenges posed by global climate change. Drawing on recent studies, we propose that not only can diet‐driven microbiome changes lead to dysbiosis, they can also shape life‐history traits and fuel human evolution. We posit that dietary shifts prompt mismatched microbiome‐host genetics configurations that modulate human longevity and reproductive success. These mismatches can also induce a heritable intra‐holobiont stress response, which encourages the holobiont to re‐establish equilibrium within the changed nutritional environment. Thus, while mismatches between climate change‐related genetic and epigenetic configurations within the holobiont increase the risk and severity of diseases, they may also affect life‐history traits and facilitate adaptive responses. These propositions form a framework that can help systematize and address climate‐related dietary challenges for policy and health interventions. Abstract : This theoretical model links disease with evolutionary adaptation through the microbiome. It explains how climate change‐induced dietary shifts can trigger dysbiosis while simultaneously encouraging the onset of adaptive traits in human holobionts. By highlighting the interplay between microbiome, epigenome, and immunity, the model provides insights that can inform medical interventions.